2011
DOI: 10.1007/s12072-011-9322-7
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization can prolong survival for patients with metastatic hepatocellular carcinoma: a propensity score matching analysis

Abstract: TACE provides survival benefit for metastatic HCC patients. Prospective randomized controlled trials are warranted to delineate the role of combining TACE with sorafenib or other treatment for metastatic HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…The diagnosis of HCC and TACE eligibility was assessed before TACE using contrast‐enhanced computed tomography (CT) or magnetic resonance imaging (MRI), which fulfilled the diagnostic criteria of the American Association for the Study of Liver Diseases (AASLD) treatment guidelines for HCC . TACE was done through selective hepatic arterial catheterization and carried out with adjuvant Adriamycin . Whenever possible, the arteries supplying the tumour(s) were catheterized super‐selectively, followed by infusion of 5‐10 mL lipiodol (Laboratoire Guerbet).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of HCC and TACE eligibility was assessed before TACE using contrast‐enhanced computed tomography (CT) or magnetic resonance imaging (MRI), which fulfilled the diagnostic criteria of the American Association for the Study of Liver Diseases (AASLD) treatment guidelines for HCC . TACE was done through selective hepatic arterial catheterization and carried out with adjuvant Adriamycin . Whenever possible, the arteries supplying the tumour(s) were catheterized super‐selectively, followed by infusion of 5‐10 mL lipiodol (Laboratoire Guerbet).…”
Section: Methodsmentioning
confidence: 99%
“…23 TACE was done through selective hepatic arterial catheterization and carried out with adjuvant Adriamycin. 22,24 Whenever possible, the arteries supplying the tumour(s) were catheterized super-selectively, followed by infusion of 5-10 mL lipiodol (Laboratoire Guerbet). The feeding arteries were then embolized with 2-3 mm strips of gelfoam (Upjohn Co.).…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study comparing standard sorafenib treatment, TACE, and TACE combined with radiation therapy in HCC patients with portal vein invasion showed that patients who underwent TACE combined with radiation therapy had longer median OS (383). Furthermore, there are retrospective studies showing that TACE is associated with survival gain, when intrahepatic HCC is treated with TACE in patients with extrahepatic metastasis (384385386). Recently, a Korean single center RCT reported that cTACE combined with radiation therapy significantly increased OS, the objective response rate (OSS), and time-to-progression (TTP) compared with sorafenib monotherapy in patients with HCC localized in the liver and portal vein invasion (387).…”
Section: Tace and Other Transarterial Therapiesmentioning
confidence: 99%
“…Surgical resection is generally recommended for HCC [6], but is indicated only for patients with early stage and well preserved liver function. For patients not suitable for curative treatment, transarterial chemoembolization (TACE) may provide better loco-regional tumor control and increase patient survival [7]. …”
Section: Introductionmentioning
confidence: 99%